Systemic antibiotics are not required for successful two-stage revision hip arthroplasty. (1st May 2023) - Petrie, Michael J.; Panchani, Sunil; Al-Einzy, Mohammad; Partridge, David; Harrison, Tim P.; Stockley, Ian
Abstract : Aims: The duration of systemic antibiotic treatment following first-stage revision surgery for periprosthetic joint infection (PJI) after total hip arthroplasty (THA) is contentious. Our philosophy is to perform an aggressive debridement, and to use a high local concentration of targeted antibiotics in cement beads and systemic prophylactic antibiotics alone. The aim of this study was to assess the success of this philosophy in the management of PJI of the hip using our two-stage protocol. Methods: The study involved a retrospective review of our prospectively collected database from which we identified all patients who underwent an intended two-stage revision for PJI of the hip. All patients had a diagnosis of PJI according to the major criteria of the Musculoskeletal Infection Society (MSIS) 2013, a minimum five-year follow-up, and were assessed using the MSIS working group outcome-reporting tool. The outcomes were grouped into 'successful' or 'unsuccessful'. Results: A total of 299 two-stage revision THAs in 289 patients met the inclusion criteria, of whom 258 (86%) proceeded to second-stage surgery. Their mean age was 68.1 years (28 to 92). The median follow-up was 10.7 years (interquartile range (IQR) 6.3 to 15.0). A 91% success rate was seen in those patients who underwent reimplantation, decreasing to 86% when including those who did not proceed to reimplantation. The median duration of postoperative systemic antibiotics following the first stage was five days (IQR 5 to 9). There was no significant difference in outcome between those patients who were treated with antibiotics for ≤ 48 hours (p = 0.961) or ≤ five days (p = 0.376) compared with those who were treated with longer courses. Greater success rates were seen for Gram-positive PJIs (87%) than for Gram-negative (84%) and mixed-Gram PJIs (72%; p = 0.098). Conclusion: Aggressive surgical debridement with a high local concentration of targeted antibiotics at the time of first-stage revision surgery for PJI of the hip, without prolonged systemic antibiotics, provides a high rate of success, responsible antibiotic stewardship, and reduced hospital costs. Cite this article: Bone Joint J 2023;105-B(5):511–517.